Overall survival and updated progression-free survival outcomes in a randomized phase II study of combination cediranib and olaparib versus olaparib in relapsed platinum-sensitive ovarian cancer. (7th February 2019) - Liu, J F; Barry, W T; Birrer, M; Lee, J -M; Buckanovich, R J; Fleming, G F; Rimel, B J; Buss, M K; Nattam, S R; Hurteau, J; Luo, W; Curtis, J; et al.
Abstract: Background: Olaparib is a poly(ADP-ribose) polymerase inhibitor and cediranib is an oral anti-angiogenic. In the primary analysis of this phase II study, combination cediranib/olaparib improved progression-free survival (PFS) compared with olaparib alone in relapsed platinum-sensitive ovarian cancer. This updated analysis was conducted to characterize overall survival (OS) and update PFS outcomes. Patients and methods: Ninety patients were enrolled to this randomized, open-label, phase II study between October 2011 and June 2013 across nine United States-based academic centers. Data cut-off was 21 December 2016, with a median follow-up of 46 months. Participants had relapsed platinum-sensitive ovarian cancer of high-grade serous or endometrioid histology or had a deleterious germline BRCA1 / 2 mutation (g BRCA m). Participants were randomized to receive olaparib capsules 400 mg twice daily or cediranib 30 mg daily and olaparib capsules 200 mg twice daily until disease progression. Results: In this updated analysis, median PFS remained significantly longer with cediranib/olaparib compared with olaparib alone (16.5 versus 8.2 months, hazard ratio 0.50; P = 0.007). Subset analyses within stratum defined by BRCA status demonstrated statistically significant improvement in PFS (23.7 versus 5.7 months, P = 0.002) and OS (37.8 versus 23.0 months, P = 0.047) in g BRCA wild-type/unknown patients, although OS was not statistically different in the overall study population (44.2 versus 33.3 months, hazard ratio 0.64; P = 0.11). PFS and OS appeared similar between the two arms in g BRCA m patients. The most common CTCAE grade 3/4 adverse events with cediranib/olaparib remained fatigue, diarrhea, and hypertension. Conclusions: Combination cediranib/olaparib significantly extends PFS compared with olaparib alone in relapsed platinum-sensitive ovarian cancer. Subset analyses suggest this margin of benefit is driven by PFS prolongation in patients without g BRCA m. OS was also significantly increased by the cediranib/olaparib combination in this subset of patients. Additional studies of this combination are ongoing and should incorporate analyses based upon BRCA status. Trial Registration: Clinicaltrials.gov Identifier NCT0111648